Investigating the urban signs for readability in today's urbanism (Case study: Mashhad Downtown, Iran) - Ahmadi, Vahid; Talebi, Farideh; Chian, Arefeh Pileh (Penerbit Universiti Kebangsaan Malaysia, 2018)
Town is a large house that should have some characteristics and benefits, so to create an attractive and lively environment it is desired to use urban elements as a leading indicator which has a significant impact on the beautiful face of the city. The use of urban indicators as a tool for organizing and saber-rattling is explicitly seen throughout history. Nowadays due to the negligence of urban design criteria the towns are dealing with reduced readability, which causes the lack of urban vision. As the human environment includes natural factors, manmade factors also provide a large part of his life. Indeed, features should be applied in the sign which will lead to their improvement. This research seeks to recognize the urban signs, and was used to collect data library and field investigations. The research method is the correlation method utilizing the mapping tool. The case study is the downtown tissue (in Mashhad of Iran) which is composed of four main streets leading to the Imam Reza Holy Shrine. Research findings were also the representation of characteristics for the urban signs of the studied region to be a background for future designs. Results showed that the visual aspects are not the only factor for the urban signs to become outstanding and a good image is based on improvement, not demolition, even at historical buildings. Thus, designers should take both sides into consideration and attempt to urban rehabilitation and improvement.